Hevein-like peptides in plants : discovery, characterization and molecular diversity - Kini Shruthi Gopalkrishna (2016)
Hevein-like peptides belong to a family of chitin-binding, cystine-knotted peptides. Based on the number of cysteine residues in hevein-like peptides they can be divided into three sub-classes, namely, 6C-, 8C- and 10C- hevein-like peptides. The objectives of my thesis are to isolate and characterize novel hevein-like peptides and to study their distribution and evolution in plants. From two herbs, Alternanthera sessilis and Moringa oleifera, six novel 6C-hevein-like peptides and three novel 8C-hevein-like peptides were isolated and purified, respectively. In addition, we gained insights into their chitin-binding interaction, anti-fungal activity and biosynthesis pathway. Using an in silico approach, a total of 385 novel hevein-like peptides were found in 124 plant families including bryophytes and gymnosperms. In conclusion, my thesis expands the existing knowledge of hevein-like peptides regarding their structure; function and biosynthesis which may help to develop robust anti-fungal agents and transgenic plants with increased specificity and resistance to fungal infections.